2022
DOI: 10.2147/tcrm.s363328
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Radiological Manifestation in Patients with Diabetes and Pulmonary Tuberculosis: A Cross-Sectional Study

Abstract: Background: Diabetes mellitus (DM) is believed to affect tuberculosis (TB) at multiple levels in disease control and treatment efficacy, but clinical and radiological presentation resulting from interaction of the two diseases is not known. Methods: A cross-sectional study was conducted on data obtained from medical records of 438 patients confirmed with TB-DM comorbidity at the Third people's hospital of Shenzhen from May 01, 2014, to April 30, 2019. Their CT images were reviewed, and patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
4
10
0
Order By: Relevance
“…Previous studies have shown that patients with TB with hyperglycemia presented with cavities, alveolar infiltrates, and fibrous tracts more frequently than those with normoglycemia 6 , 37 . However, the results of this study are contrary, and no significant effect of hyperglycemia on pulmonary lesions in patients with TB was found after controlling for confounding factors.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that patients with TB with hyperglycemia presented with cavities, alveolar infiltrates, and fibrous tracts more frequently than those with normoglycemia 6 , 37 . However, the results of this study are contrary, and no significant effect of hyperglycemia on pulmonary lesions in patients with TB was found after controlling for confounding factors.…”
Section: Discussionmentioning
confidence: 94%
“…There are many studies [ 8 , 9 , 17 , 26 ] suggesting that TB-DM patients have lesions primarily in the lower lungs and involving more lobes. In contrast, our results showed no statistical difference between the TB-DM and DM groups in terms of the location of the TB lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Two experienced radiologists reviewed the CT images and reached a consensus decision at the Third People's Hospital of Shenzhen. The definition of pulmonary cavitation can be referred in this article ( 3 ), and a representative CT image is displayed in Supplementary Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes, as a metabolic disorder disease, is associated with innate and adaptive immune dysfunctions and alterations in specific cytokines and chemokines (2). Previous studies have reported a paradoxical hyperinflammatory response in TB patients with DM, such as IFN-γ, IL-2, and TNF-a (3)(4)(5). There were studies indicating that diabetes mellitus (DM) is associated with an increased risk of TB (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%